Modelling, simulation and testing of steer-by wire system with variable steering ratio control strategy in 14-DOF full vehicle model - Ahmad, Fauzi; Azizul, Muhamad Asri; Karjanto, Juffrizal; Che Hasan, Mohd Hanif; Sulaiman, Syabillah (Universiti Malaysia Pahang, 2024)
This research explores the application of Proportional-Integral-Derivative (PID) controllers and Variable Steering Ratio (VSR) control strategies within a Steer-by-Wire (SbW) system, utilizing a comprehensive 14 Degrees of Freedom (DOF) full vehicle dynamic model. The study aims to advance vehicle dynamics and control through SbW technology. This research addresses the challenge of optimizing steering control by integrating an SbW system with PID and VSR strategies to overcome the limitations of traditional steering mechanisms and enhancevehicle responsiveness and stability. The SbW system, using a PID-based controller, was rigorously tested and validated using MATLAB Simulink and Hardware-in-the-Loop System (HiLS) method. The performance of the system was assessed through four distinct signal tests: step, sine, square, and sawtooth inputs. These tests confirmed the precision of the PID controller in position tracking. To improve the practical applicability of the SbW system, a 14-DOF vehicle dynamic model was developed and validated before integration with the SbW system. The integrated system accurately replicated conventional steering behavior, as validated by Step Steer Input (SSI) and Double Lane Change (DLC) tests, demonstrating less than 11% RMS percentage error -well within the acceptable threshold of less than 15%. Additionally, the study proposed and validated VSR control strategies through the DLC test. Results indicate that the PID controller effectively tracked desired signals, while the VSR strategy reduced driver workload and improved steering stability. This research offers valuable insights into enhancing SbW system performance and lays a foundation for future advancements in vehicle control systems.